Effects of Pandemic on Feelings of Depression in Italy: The Role of Age, Gender, and Individual Experiences During the First Lockdown - Arpino, Bruno; Pasqualini, Marta (Frontiers in Psychology, 2021)
The restrictions to physical contacts that have been imposed in different countries to deal with the coronavirus disease 2019 (COVID-19) pandemic may have contributed to an increase in feelings of depression on top of other negative consequences of the pandemic. This study examines the consequences of the COVID-19 pandemic on feelings of depression using original data collected in Italy between April 14 and 24, 2020. Quota sampling (N = 3,026) was performed to target the population of 18+ and, together with post-stratification weights, permitted obtaining a representative sample of the Italian population with respect to key sociodemographic factors. We find that 47% of the respondents have increased depressive feelings during the Covid-19 lockdown. Adopting a life-course perspective, we revealed great heterogeneity in feelings of depression consequences by age, gender, and difficulties experienced during the first national lockdown. Identifying groups of population at higher risk of suffering from feelings of depression as a result of COVID-19 is crucial to limit indirect long-term consequences of the pandemic.